Cutaneous Microenvironment of Human Immunodeficiency Virus (HIV)-Seropositive and HIV-Seronegative Individuals, with Special Reference to Staphylococcus aureus Colonization - Shapiro, Michael (American Society for Microbiology, 2000)
A cross-sectional quantitative study of cutaneous bacterial and yeast flora at seven body sites in 99 human immunodeficiency virus-seropositive and 50 seronegative military personnel was performed. Statistically significant differences in carriage rates were only observed for Staphylococcus aureus on the foreheads of seropositive individuals. Seronegative individuals demonstrated staphylococcal carriage rates 1.3 to 2 times as great as those of historical controls (defined as healthy individuals not receiving any medications) at five of six body sites. We conclude that seropositive military personnel do not exhibit statistically significant elevations in densities and carriage rates of the microorganisms examined (except Staphylococcus aureus), relative to seronegative individuals. Seropositive individuals may be predisposed to staphylococcal carriage. The elevated staphylococcal carriage rates of military personnel undergoing basic training warrants a formal evaluation of the impact of training exercises on cutaneous flora. The information gained may serve to limit the spread of infection during training exercises and battlefield conditions.